2004
DOI: 10.1186/1471-2180-4-32
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Gram-negative bacteria cause most nosocomial respiratory infections. At the University of Cumhuriyet, we examined 328 respiratory isolates of Enterobacteriaceae and Acinetobacter baumanii organisms in Sivas, Turkey over 3 years. We used disk diffusion or standardized microdilution to test the isolates against 18 antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 17 publications
4
9
1
1
Order By: Relevance
“…Similarly (Khanfar et al, 2009) reported 17% ESBL positive K. pneumoniae strains from nosocomial and community-acquired infections and all ESBL positive isolates were sensitive to imipenem while in contrast to present study resistant to gentamicin and ciprofloxacin. Findings of present study is also supported by (Gonlugur et al, 2004) with little less frequency (12%) of ESBL producing K. pneumoniae strains from specimen of respiratory tract infected humans and also found that ESBL producing isolates were sensitive to imipenem and ciprofloxacin with more resistance to tetracycline. (Zhou et al, 2011) reported antibiotic resistance pattern and ESBL activity of K. pneumoniae isolated from randomly purchased powdered infant formula and found that 16.6 % isolates were ESBL producers with 100% resistance towards oxacillin and sensitivity for ciprofloxacin and gentamicin, a similar finding in this investigation.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly (Khanfar et al, 2009) reported 17% ESBL positive K. pneumoniae strains from nosocomial and community-acquired infections and all ESBL positive isolates were sensitive to imipenem while in contrast to present study resistant to gentamicin and ciprofloxacin. Findings of present study is also supported by (Gonlugur et al, 2004) with little less frequency (12%) of ESBL producing K. pneumoniae strains from specimen of respiratory tract infected humans and also found that ESBL producing isolates were sensitive to imipenem and ciprofloxacin with more resistance to tetracycline. (Zhou et al, 2011) reported antibiotic resistance pattern and ESBL activity of K. pneumoniae isolated from randomly purchased powdered infant formula and found that 16.6 % isolates were ESBL producers with 100% resistance towards oxacillin and sensitivity for ciprofloxacin and gentamicin, a similar finding in this investigation.…”
Section: Discussionsupporting
confidence: 85%
“…The resistance may also be due to the production of Metallo-B-Lactamases (MBL) which can be chromosomally encoded or plasmid mediated (Navaneeth et al, 2002;Hancock, 1998). Our results are supported by Forster and Daschner (1998) and Gonlugur et al (2004) in their studies showing varying resistance (4-60%) of Pseudomonas towards these drugs across the World.…”
Section: Discussionsupporting
confidence: 62%
“…The emergence of carbapenem resistance is a serious concern 24 . In various studies across the world, varying rates of resistance from 4-60% have been reported for imipenem and meropenem 25 . Another survey found that resistance to imipenem was 19%, while other studies have reported low rates (5.8% and 9%) and high rates (38.6%) of resistance to imipenem 26 .…”
Section: Figure 4: Distribution Of P Aeruginosa Isolates According Tmentioning
confidence: 99%